THE INFLUENCE OF PERFORMANCE, AGE, AND NATIONALITY ON THE MARKET VALUE OF FOOTBALL PLAYERS - Loggar Bhilawa; Ryanaldi Fahriansyah (Universitas PGRI Madiun, 2022)
ABSTRACTThis research aims to investigate the influence of performance, age, and nationality on the market value of football players. The population in this research is the professional football players that play in Indonesian League 1 competition in the 2019 season. Data obtained from the official website that publishes the football players' prices in the transfer market in the world is transfermarkt.co.uk. The purposive random sampling method obtained samples from as many as 234 professional football players from 18 clubs. This research used a quantitative approach. The results of this research show that the performance has a positive effect on the market value of football players because the market value of the players reflects the performance of the players themselves. At the same time, age also harms the market value of soccer players because age affects the performance of football players. Nationality has a positive effect on the market value of football players because nationality influences the quality and ability of football players. In this research, we show that players with good performance are more interested in many clubs at a young age, so these players have a high market value.ABSTRAKTujuan penelitian ini untuk menguji pengaruh performance, umur, dan nationality terhadap market value pemain sepakbola. Populasi adalah pemain sepakbola professional yang bermain di Liga 1 Indonesia musim 2019. Data diperoleh dari situs transfermarkt.co.uk. Berdasarkan metode purposive random sampling, sampel yang diperoleh sebanyak 234 pemain pada 18 klub. Penelitian ini menggunakan metode pendekatan kuantitatif. Hasil penelitian ini menunjukkan performance berpengaruh positif terhadap market value pemain sepakbola, sedangkan umur berpengaruh negatif terhadap market value pemain sepakbola, dan nationality berpengaruh positif terhadap market value pemain sepakbola. Penelitian ini menunjukkan bahwa pemain dengan performance yang baik dan umur yang masih muda lebih diminati oleh banyak klub sehingga pemain tersebut memiliki nilai pasar yang tinggi.